Clinical and instrumental assessment of the corneal healing in moderate and severe neurotrophic keratopathy treated with rh-NGF (Cenegermin). Issue 6 (November 2022) - Roszkowska, Anna M; Inferrera, Leandro; Aragona, Emanuela; Gargano, Romana; Postorino, Elisa I; Aragona, Pasquale
Purpose: To evaluate corneal healing in patients with moderate and severe neurotrophic keratitis (NK) treated with topical rh-NFG (Cenegermin). Methods: Twenty-one patients (12F and 9M) aged from 21 to 93 years (62.5 ± 19.4) with moderate and severe NK were enrolled in the study. The patients were divided into 2 groups accordingly to the severity of the disease. The underlying causes of NK were determined. The VAS questionnaire was dispensed. The ocular examination comprised slit lamp evaluation, ocular surface assessment with Keratograph 5M (Oculus, Germany), corneal sensitivity with Cochet-Bonnet esthesiometer (Lunneaux, France) and corneal thickness measurement with AC-OCT (DRI, Triton, Topcon, Japan). The drops of Cenegermin 0.002% were administrated 6 times daily for 8 weeks. All participants were evaluated at baseline, after 4 and 8 weeks of the treatment. The area of corneal defect with maximum diameter less than 0.5 mm was considered as healed. The main outcome measures were corneal healing, corneal sensitivity recovery and corneal thickness in the ulcer group. Results: The herpetic keratitis was the most common cause of NK. Thirteen eyes were affected by severe grade of NK with corneal ulcer and 8 eyes presented a moderate grade. After 8 weeks a complete healing of the corneal defects was registered both in moderate and severe NK. Significant increase of the corneal sensitivity and thickness were registered. Conclusions: The rh-NGF (Cenegermin) resulted effective in the treatment of the severe and moderate NK with significant recovery of the corneal sensitivity and healing of the corneal defects in both groups.